2020
DOI: 10.1111/jop.13090
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes associated with malignant transformation of oral potentially malignant disorders

Abstract: Background A large number of oral squamous cell carcinomas (OSCCs) are believed to be preceded by oral potentially malignant disorders (OPMD) that have an increased likelihood of malignant transformation compared to clinically normal mucosa. This study was performed to identify differentially expressed genes between OPMDs that underwent malignant transformation (MT) and those that did not, termed “non‐transforming” (NT) cases. Methods Total RNA was extracted from formalin‐fixed paraffin‐embedded tissue biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In the future, high-resolution molecular techniques may provide the information required to improve prognostic accuracy. 40,41 There was a low prevalence of HPVOED in this cohort (2.3%) compared with the 27.2% published in a recent meta-analysis on prevalence of HPV in OED. 42 The high prevalence values in the studies included in the meta-analysis could be due to the use of polymerase chain reaction (PCR)-based techniques as the method to detect HPV DNA.…”
Section: Discussionmentioning
confidence: 49%
“…In the future, high-resolution molecular techniques may provide the information required to improve prognostic accuracy. 40,41 There was a low prevalence of HPVOED in this cohort (2.3%) compared with the 27.2% published in a recent meta-analysis on prevalence of HPV in OED. 42 The high prevalence values in the studies included in the meta-analysis could be due to the use of polymerase chain reaction (PCR)-based techniques as the method to detect HPV DNA.…”
Section: Discussionmentioning
confidence: 49%
“…Some of the genes upregulated in this pathway include DLK1 and DLX2 . These genes have been found to be involved in the malignant transformation and progression of many tumours, including OSCC [ 36 , 37 , 38 ]. All these results provide compelling evidence that our preclinical model is valid and accurately represents tobacco-induced OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A list of target genes for the NanoString nCounter Customised Panel (42 genes; 38 target and 4 housekeeping genes) was compiled based on the results of previous experiments: a whole-transcriptome analysis with total RNA sequencing (RNA-Seq), 35 results of previous differential gene expression work performed by our group and review of published literature. The selection of candidate genes was discussed and finalised through consensus by the authors; the gene list is shown in Supplementary Table 1.…”
Section: Nanostring Ncounter Customised Panelmentioning
confidence: 99%